2009
DOI: 10.1007/978-0-387-77064-2_30
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of Human Finger Muscles after Stroke or Amputation

Abstract: Individuated finger movements of the human hand require selective activation of particular sets of muscles. Such selective activation is controlled primarily by the motor cortex via the corticospinal tract. Is this selectivity therefore lost when lesions damage the corticospinal tract? Or when the motor cortex reorganizes after amputation? We studied finger movements in normal human subjects and in patients who had recovered substantially from pure motor hemiparesis caused by lacunar strokes, which damage the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 61 publications
2
47
1
1
Order By: Relevance
“…The quantification of discrete changes in M1 excitability is also relevant for clinical research, e.g. in patients with Stroke, Parkinson's disease or Focal Hand Dystonia who show an altered pattern of M1 HAND representation/function and dynamical muscular representation (Beck et al, 2009;Granert et al, 2011;Schieber et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The quantification of discrete changes in M1 excitability is also relevant for clinical research, e.g. in patients with Stroke, Parkinson's disease or Focal Hand Dystonia who show an altered pattern of M1 HAND representation/function and dynamical muscular representation (Beck et al, 2009;Granert et al, 2011;Schieber et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, the central nervous system (CNS) tends to select certain families of solutions, or synergies, when grasping objects (Santello and Soechting, 2000;Rearick and Santello, 2002;Shim et al, 2003Shim et al, , 2005aJohnston et al, 2005Johnston et al, , 2010Shim and Park, 2007). A better understanding of such control mechanisms can lead to improved rehabilitation of neuromuscular dysfunction (Nowak, 2008;Alberts and Wolf, 2009;Schieber et al, 2009), and the development of more dextrous robotic limbs (Bae et al, 2005;Choi et al, 2008;Lee et al, 2009;Yang et al, 2009). …”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have administered digital anesthesia as a primary modality to remove cutaneous feedback from the digits and investigated the role of cutaneous feedback on CNS control over hand and finger actions (Gandevia and McCloskey, 1977;Kilbreath et al, 1997;Reilly et al, 2008;Schieber et al, 2009). Studies on sub-maximal force production tasks such as grasping and pinching have shown that effective removal of cutaneous feedback leads to an increase in errors during motor performance (Nowak et al, 2001;Monzee et al, 2003).…”
Section: Introductionmentioning
confidence: 99%